Pharmacoeconomic analysis of thrombopoietin receptor agonists in the treatment of chronic idiopathic thrombocytopenic purpura in adults - E. A. Pyadushkina; M. Yu. Frolov; V. A. Shuvaev; V. A. Rogov (Izdatelstvo OKI, 2018)
Actuallity. Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease caused by the production of antibodies to the platelet and megakaryocytes membrane structure, which causes to increase the platelet destruction, but also inadequate thrombocytopoiesis. e disease is characterized by a significant loss of ability to work and decreasing quality of life, higher mortality rate, as well as frequent hospitalizations, reecting to health care resources utilization. Therefore, burden of disease assessment is a point of high interest. Methodology. Two pharmacoeconomic models were developed for the "cost-minimization" and "budget impact" analysis on the basis of Microso Excel soware. e modeling hypothesis is comparable efficacy and safety of thrombopoietin receptor agonists (TPO), based on the absence of statistically significant differences from the results of an indirect comparison and the efficacy of romiplostim is assumed to be equal to the efficacy of eltrombopag. Direct medical costs were calculated based on the costs of drugs from the TPO receptor agonist group, the administration of drugs, «rescue therapy», bleeding treatment, and follow-up monitoring of patients with ITP during therapy. Calculations were based on registered limit transfer drug prices from the VED List and standards of the financial expenses per medical care volume unit of Russian Federation in 2018. e reduction in costs per patient per year is 796,967 rubles (33 %). Results. Clinical and economic analysis of drugs from the group of thrombopoietin receptor agonists in the therapy of chronic idiopathic thrombocytopenic purpura in adults has shown that eltrombopag in comparison with romiplostim in patients with chronic ITP at the background of previous treatment failure is more economically expedient being not less clinical effective. It is possible to reduce the budget impact of the healthcare system of the Russian Federation by 1,693 million rubles (8 %) for 5 years with the gradual increasing in eltrombopag share in the purchase of TPO receptor agonists. Conclusion. Eltrombopag with comparable efficacy and safety is more economically sound option of chronic ITP treatment as compared to romiplostim.